DEVELOPING THE SONG TO TEACH LANGUAGE COMPONENTS FOR THE SEVENTH GRADERS OF SMP WAHID HASYIM MALANG - GANJARSARI, RIMA DAMAI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: teaching English as foreign language (TEFL), beginner level of students, teaching media, teaching materials, song.English and Bahasa Indonesia have different language systems, such as in vocabulary, pronunciation, and grammar. Those differences make the students in Junior High School that can be categorized as beginner level of the students, are considering getting difficulty. In addition, the newest curriculum, Kurikulum 2013, which consists of many materials in one chapter also make the students are considering to get bore. Those problems are also found in 7B class of SMP Wahid Hasyim Malang. Therefore, the teacher should provide interesting media and material to the students. By this study, the writer conducts a research in developing the song to teach language components for the seventh graders of SMP Wahid Hasyim Malang. The problem that will be answered by this study is how to develop the song to teach language components for the seventh graders of SMP Wahid Hasyim Malang?This study uses R&D as the research design. There are eight procedures in this study, namely needs analysis, planning, media and material development, expert validation, revision 1, try out, revision 2, and final product which are adapted from Borg and Gall (1983) and Lee (2013). The writer uses descriptive qualitative as the approach in order to explain systematic description about the procedures in developing the song. This study provides systematically explanations about each procedures in developing the song. Firstly, in needs analysis step reveals that the students’ problems are lack in mastery vocabulary, pronunciation, and grammar. Secondly, in planning step, the writer sets the objective of the song, choose the devices, choose the experts, choose the collaborator, and make an estimation of the time. Thirdly, developing the song using familiar melody of “Goyang Dumang” and change the lyrics through four kinds of programs, namely Adobe Audition, Audacity, Movie Maker, and Subtitle Edit. Fourthly is passing the expert validation and try out step and getting the feedback ofthem. Finally, the song to teach language components is developed by the writer inorder to answer the problem of the study.The writer gives some suggestions for the students and English teacher in 7B class of SMP Wahid Hasyim Malang, for the English teacher who teach TEFL, and for the next research, better to use this study to support the learning activity and use this product as the guideline to develop another interesting material, media, exercises, and research.